Aspek Etika dan Tanggung Jawab Penggunaan Artificial Intelligence dalam Meningkatkan Kualitas Pembelajaran di Lembaga Pendidikan TNI Angkatan Laut - Heru Nur Cahyo; Elisabeth Tanti P; Mohammad Rachmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The digital transformation in education has extended into military institutions, including the Indonesian Navy’s (TNI AL) educational system, which consists of Kodiklatal, AAL, Seskoal, and STTAL. This study aims to analyze the implementation of Artificial Intelligence (AI) in military education and to identify its benefits, challenges, and strategic development approaches. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews, document analysis, and limited observations. The findings indicate that AI holds significant potential to enhance learning efficiency, personalize content delivery, and improve real-time evaluation. However, several ethical and technical challenges arise, particularly regarding data privacy, infrastructure readiness, and cultural resistance among educators. This study recommends the development of ethical guidelines based on the principles of transparency and privacy, the enhancement of digital literacy among instructors, and the adoption of hybrid learning approaches that balance technological innovation with the core values of military education. With the right strategies, AI can become a powerful tool to support the formation of TNI AL officers who are professional, intelligent, and morally grounded.